1991
DOI: 10.1104/pp.96.4.1268
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Small Heat Shock Protein Gene from Maize

Abstract: A maize (Zea mays L.) genomic clone (Zmempr 9') was isolated on the basis of its homology to a meiotically expressed LIfium sequence. Radiolabeled probe made from the maize genomic clone detected complementary RNA at high fidelity. Furthermore, it hybridized to RNA isolated from staged (an interval that is coincident with meiotic prophase) maize tassel spikelets. Complimentary RNA was strongly (at least 50-fold) induced during heat shock of maize somatic tissue and appeared as a single size class in Northern b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Our data at the protein level extend those of Dietrich et al (1991) and Atkinson et al (1993) who reported developmental regulation of specific HSP18 mRNAs during maize male development and particularly their accumulation in anthers near meiosis. In addition, our data indicate that most of the members of the maize microspore lowmolecular-mass HSP family are likely to be very stable, since they were present at the control temperature on immunoblots and were not detected on 28°C fluorograms.…”
Section: Expression Of Microspore Hsps At Non-heat-shock Temperaturesupporting
confidence: 89%
See 1 more Smart Citation
“…Our data at the protein level extend those of Dietrich et al (1991) and Atkinson et al (1993) who reported developmental regulation of specific HSP18 mRNAs during maize male development and particularly their accumulation in anthers near meiosis. In addition, our data indicate that most of the members of the maize microspore lowmolecular-mass HSP family are likely to be very stable, since they were present at the control temperature on immunoblots and were not detected on 28°C fluorograms.…”
Section: Expression Of Microspore Hsps At Non-heat-shock Temperaturesupporting
confidence: 89%
“…During maize male development, such HSP gene expression has been reported at meiosis (Dietrich et al, 1991;Atkinson et al, 1993;Bouchard et al, 1993;Marrs et al, 1993). As with meiosis, first pollen mitosis is a key event of pollen formation (McCormick, 1993;Eady et al, 1995).…”
mentioning
confidence: 99%
“…In most cases, papers report only on the detection of HSP20 mRNAs in developing seeds (Pitto et al 1983;Davies and Grierson 1989;Helm and Abernethy 1989;Vierling and Sun 1989;Zimmerman et al 1989;Fray et al 1990;Gy6rgyey et al 1991;Almoguera and Jordano 1992;Koning et al 1992;Atkinson et al 1993;Kruse et al 1993) and meiotic stages of pollen development, respectively (Xiao and Macarenhas 1985;Schrauwen et al 1986;VanHerpen et al 1989;Bouchard 1990;Dietrich et al 1991). The corresponding HSPs were only rarely investigated (Hernandez and Vierling 1993;DeRocher and Vierling 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of environmental stress, synthesis of HSPs in plants is restricted to certain stages of development. The mRNAs for small HSPs (sHSPs) were detected during meiotic prophase in lily [3] and maize [6] and during microsporogenesis in maize [2] and tobacco [22]. HSPs and the corresponding mRNAs were found in embryos of wheat [9], and the embryonic expression of sHSP genes was reported for pea [5], sunflower [1, 4], Arabidopsis, and tobacco [ 16].…”
mentioning
confidence: 99%